Tunable metacrylated hyaluronic acid-based hybrid bioinks for stereolithography 3D bioprinting. (27th September 2021) - Hossain Rakin, Rafaeal; Kumar, Hitendra; Rajeev, Ashna; Natale, Giovanniantonio; Menard, Frederic; Li, Isaac T S; Kim, Keekyoung
Abstract: Hyaluronic acid is a native extra-cellular matrix derivative that promises unique properties, such as anti-inflammatory response and cell-signaling with tissue-specific applications under its bioactive properties. Here, we investigate the importance of the duration of synthesis to obtain photocrosslinkable methacrylated hyaluronic acid (MeHA) with high degree of substitution. MeHA with high degree of substitution can result in rapid photocrosslinking and can be used as a bioink for stereolithographic (SLA) three dimensional 3D bioprinting. Increased degree of substitution results Our findings show that a ten-day synthesis results in an 88% degree of methacrylation (DM), whereas three-day and five-day syntheses result in 32% and 42% DM, respectively. The rheological characterization revealed an increased rate of photopolymerization with increasing DM. Further, we developed a hybrid bioink to overcome the non-cell-adhesive nature of MeHA by combining it with gelatin methacryloyl (GelMA) to fabricate 3D cell-laden hydrogel scaffolds. The hybrid bioink exhibited a 55% enhancement in stiffness compared to MeHA only and enabled cell-adhesion while maintaining high cell viability. Investigations also revealed that the hybrid bioink was a more suitable candidate for stereolithography (SLA) 3D bioprinting than MeHA because of its mechanical strength, printability, and cell-adhesive nature. This research lays out a firm foundation for the development of a stable hybrid bioink with MeHA and GelMA for first-ever use with SLA 3D bioprinting.